FACTORS ASSOCIATED WITH FAMILY RESILIENCE AMONG HEMODIALYSIS PATIENTS: A CROSS-SECTIONAL STUDY - Dwi Ayu Lestari; Nety Mawarda Hatmanti; Lono Wijayanti; Nunik Purwanti; Destyorini Suryandari (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Family resilience plays a crucial role in maintaining psychological well-being and adaptive coping among families caring for hemodialysis patients. Chronic illness and prolonged treatment often impose emotional and physical burdens that challenge the family’s ability to adapt, highlighting the need to identify determinants influencing resilience. Objective: This study aimed to analyze the relationships between demographic and clinical factors: age, gender, education level, duration of hemodialysis, and comorbidities, and family resilience among patients undergoing hemodialysis at Ahmad Yani Islamic Hospital, Surabaya, Indonesia. Methods: This study used a correlational analytic design with a cross-sectional approach. The population included 110 hemodialysis patients, and 86 respondents were selected using simple random sampling. Independent variables included age, gender, education level, duration of hemodialysis, and comorbidities, while the dependent variable was resilience. The Connor–Davidson Resilience Scale (CD-RISC) was used to measure resilience. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. Result: Most respondents (88.4%) demonstrated a very high level of resilience. Significant relationships were found between resilience and gender (p = 0.002), education level (p < 0.001), duration of hemodialysis (p < 0.001), and comorbidities (p < 0.001), while age showed no significant association (p = 0.019). Conclusion: Family resilience among hemodialysis patients was classified as very high. Socio-demographic factors, health conditions, and treatment duration influenced resilience levels. These findings highlight the need for nursing interventions focusing on psychosocial support, patient education, and family empowerment to enhance adaptive coping in long-term hemodialysis care.